2022
DOI: 10.28991/esj-2022-06-05-09
|View full text |Cite
|
Sign up to set email alerts
|

Fitting Multi-Layer Feed Forward Neural Network and Autoregressive Integrated Moving Average for Dhaka Stock Exchange Price Predicting

Abstract: The stock market plays a vital role in the economic development of any country. Stock market performance can be measured by the market capitalization ratio as well as many other factors. The primary purpose of this study is to predict the movement of the stock market based on the total market capitalization of the Dhaka Stock Exchange (DSE) using autoregressive integrated moving average (ARIMA) models as well as artificial neural networks (ANN). The data set covers monthly time series data of total market capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…This study revealed that the community, customers, employees, organizational commitment are the significant factors for improving performance. On the other hand, the corporate reputation also moderates the (Kader et al, 2021;Kabir et al, 2021;Mia et al, 2022;Rubi et al, 2022;Shahriar et al, 2021) relationship between customers to organizational performance, employees to organizational performance, commitment to performance and the employees to performance. Therefore, the corporate social responsibility plays significant role to create organization performance.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…This study revealed that the community, customers, employees, organizational commitment are the significant factors for improving performance. On the other hand, the corporate reputation also moderates the (Kader et al, 2021;Kabir et al, 2021;Mia et al, 2022;Rubi et al, 2022;Shahriar et al, 2021) relationship between customers to organizational performance, employees to organizational performance, commitment to performance and the employees to performance. Therefore, the corporate social responsibility plays significant role to create organization performance.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…There needs to be more research on performance evaluation for individual organization across the whole power sector (Dong et al, 2021). Financial ratios are used in multi-decision analysis to assess the financial performance of power-producing businesses (Lkuçar & Ifci, 2016;;Faisal-E-Alam et al, 2022;Khan et al, 2022;Mia et al, 2022;Rubi et al, 2022;Zayed et al, 2022a;Zayed et al, 2022b). When evaluating a company's financial success, one can look at either the absolute performance in terms of the scope of operations (balance sheet and income statement) or the relative performance in terms of financial ratios (Katchova & Enlow, 2013;Vibhute et al, 2021;Ali et al, 2020a;Ali et al, 2020b;Chowdhury et al, 2020;F.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consistency throughout the year not only enhances the probability that a product or service will operate as expected, but it also assures on-time delivery. This assists in (Khan et al, 2022a;Khan et al, 2022b;Mia et al, 2022;Rubi et al, 2022)detecting customer experience indicators and potential risks of losing business to competition. Tanzania, which has six fully-fledged Islamic banks, identified the benefits of corporal efficiency, trust, core banking services, and other factors.…”
Section: Literature Reviewmentioning
confidence: 99%